2018
DOI: 10.1113/ep087115
|View full text |Cite
|
Sign up to set email alerts
|

Determining day‐to‐day human variation in indirect calorimetry using Bayesian decision theory

Abstract: New Findings What is the central question of this study?We sought to understand the day‐to‐day variability of human indirect calorimetry during rest and exercise. Previous work has been unable to separate human day‐to‐day variability from measurement error and within‐trial human variability. We developed models accounting for different levels of human‐ and machine‐level variance and compared the probability density functions using total variation distance. What is the main finding and its importance?After acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Many previous studies have reported day-to-day variation in V O 2 max [6][7][8][9][10]. For example, it has been reported that day-to-day variation in V O 2 max determined by a graded power test using a cycle ergometer [10] or treadmill [6] was around 6% in healthy young adults, with no sex difference.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have reported day-to-day variation in V O 2 max [6][7][8][9][10]. For example, it has been reported that day-to-day variation in V O 2 max determined by a graded power test using a cycle ergometer [10] or treadmill [6] was around 6% in healthy young adults, with no sex difference.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, REE measurements in general are quite noisy due to slight differences between the measurements (e.g., closing of canopy and calibration artefacts) (Tenan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%